Effect of Health Education Video on Knowledge about Stunting among Women in Childbearing Age - Annisa Nuraini; Puspa Sari; Sri Astuti; Lani Gumilang; Didah Didah (Althea Medical Journal, 2021)
Background: Toddlers aged 24-59 months are experiencing a very rapid growth process; however, they are also prone to have nutritional problems, including stunting. Stunting occurs mainly within the first 2 to 5 years of life. The main cause is a lack of knowledge on toddler’s nutritional intake among women of childbearing age. This study aimed to explore the effect of health education using video media on the knowledge about stunting among women of childbearing age.Methods: This was a quantitative, experimental study with one group pretest-posttest design conducted in July-November 2019 on women of childbearing age in the working area of Public Health Center (Pusat Kesehatan Masyarakat, Puskesmas) Jatinangor, West Java, Indonesia. Respondents were recruited using the Multistage Random Sampling according to the inclusion criteria. A pre-test was administered before the health education session on stunting and a post-test was administered afterwards. Data collected were then analyzed using the Wilcoxon Test.Results: In total, 211 women were included. Education video on stunting was proved to significantly increase the respondent's knowledge on stunting (p=0.000, r value=0.690).Conclusion: Health education video clearly increases knowledge on stunting among women of childbearing age. Thus, video medium can be used as a preferred method for disseminating knowledge on various health topics.